Teoretyczna analiza koncepcji międzykulturowej kompetencji komunikacyjnej - Terekhova, Tatyana A.; Bolshakova, Olesya B. (Studia Europaea Gnesnensia, 2016)
The paper presents an overview discussion of the conceptualizations of intercultural communicative competence (ICC) formulated by Russian scholars. The conceptions of the ICC are quite diverse as well as terminology used by the scholars. The authors place emphasis on the psychological aspects of the ICC, distinguishing psycho- physiological, personality, socio-psychological and psycho-pedagogical levels of its analysis.